Evaluación del desgaste de prótesis cerámicas de cadera recubiertas con DLC por triboadhesión Parte I - Diseño de la máquina de deposición y desgaste - Rodríguez Lelis, J. M.; Abúndez P., A.; Abúndez P., Claudia; Chinchilla G, S. (Revista Mexicana de Ingenieria Biomedica, 2006)
In this paper it is presented the design of a dual device aimed to carry out film coatings by triboadhesion and wear assessment of hip prosthesis. The coating device was designed with three degrees of freedom in such a way that only the upper hemisphere of the prosthesis femoral head could be coated. On the other hand, the wear device was designed as an interchangeable section of the coating device, and the movement trajectories described by the prosthesis and the loads applied to the prosthesis were obtained from the ISO 14-242-1 standard.